THE PRACTICE OF EIGHT FAMILY FUNCTIONS: DIFFERENCES BETWEEN RURAL AND URBAN AGING FAMILIES IN INDONESIA - Pujihasvuty, Resti; Nasution, Sri Lilestina; Naibaho, Margareth Maya P; Fajarningtiyas, Desy Nuri (Jurnal Ilmu Keluarga dan Konsumen, 2023)
The family is essential in improving the older adults’ quality of life, where the family's role can be reflected in the eight family function practices: 1) Religious; 2) Sociocultural; 3) Love; 4) Protection; 5) Reproductive; 6) Socio-education; 7) Economic; and 8) Environmental. This study aimed to determine the differences in family function practices among aging families in rural and urban areas. Data were analyzed using Cross-Tabulation with the Chi-Square and Independent T-test from a sample of 12,391 aging families in the 2019 Program Accountability Performance Survey. The results of the Independent T-test p